Fast FPGA prototyping toolbox for embedded optimization - Suardi,A; Kerrigan,EC; Constantinides,GA (IEEE, 2015)
Traditionally compute-intensive optimisation algorithms have been implemented on CPU based machines, primarily in order to reduce development time, but sacrificing computing speed and energy consumption. However, recent advancements in FPGA technologies are making the design effort comparable to that of CPUs, making them an increasingly viable option. This paper presents FPGA IP prototyping toolbox (PROTOIP), which is an Open Source framework conceived to enable researchers and engineers to design, validate and prototype algorithms quickly on FPGA platforms. Abstracting many low-level FPGA design details, PROTOIP provides custom templates, scripts, example designs and tutorials specifically tailored for embedded optimization applications.